Kajian Pengaruh Paparan Medan Magnet terhadap Indeks Mitosis Sel Akar Bawang Putih (Allium sativum L.) Lokal Asal Timor - Gede Arya Wiguna; Dicky Frengki Hanas; Welsiliana (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Garlic is a horticultural plant that is used as a flavoring and also has pharmacological benefits. Local Timor Garlic, known as Eban Garlic, is one of the local varieties of garlic from Indonesia. Eban garlic is one of the leading commodities in North Central Timor Regency whose cultivation is carried out for generations. To increase the yield of garlic, the growth and development of these plants must be considered. Growth and development are part of the biological processes of organisms. In plants, primary growth occurs at the growing point, namely the meristematic tissue at the tip of the shoot and the tip of the plant root. In this article, we will examine the effect of exposure to magnetic fields on the mitotic index of Eban garlic root tip cells. The results showed that the greater the exposure to a given magnetic field, the smaller the mitotic index. The control treatment had the highest mitotic index of 36.56% and exposure to a magnetic field of 20.03 mT had the lowest mitotic index of 20.03%. The results of the study based on the time of observation, the prophase phase had the greatest mitotic index, which was 84.21% in the control treatment. This means that exposure to a magnetic field that is too high can slow down the cell division of Eban garlic roots.